PENJABARAN HUKUM ALAM MENURUT PIKIRAN ORANG JAWA BERDASARKAN PRANATA MANGSA - Rini Fidiyani; Ubaidillah Kamal (Faculty of Law, Universitas Jenderal Soedirman, 2012)
Pranara mangsa is a local knowledge on the management of agricultural land for the Javanese people. This study aimed to determine the ability of Jawva to read the laws of nature and the existence of pranata mangsa on people Banyumas today. What is there in nature is a manifestation of God’s eternal law that by Him manifested in signs of nature. How to interpret the laws of nature by which Java is used as a benchmark in managing land called pranata mangsa.Pranata mangsa are dynamic institution, especially with the uncertain climate change. For farmers Banyumas, pranata mangsa remains a benchmark, but as the development of science and technology, pranata mangsa becoming obsolete. This is a threat to the existence of pranata mangsa as national heritage. Key words: pranata mangsa, anthropology of law, natural law, the Javanese